Barriers of achieving and maintaining glycemic target among patients with type 2 diabetes mellitus on insulin therapy (BIRDEM Medical Journal, 2025)
Background: Many obstacles exist that lead to failure of achievement of glycemic target in persons with diabetes mellitus (DM) prescribed with insulin. However, there is an inadequate amount of data to address these barriers and to make effective intervention. The aim of this study was to identify barriers of achieving and maintaining glycemic target among type 2 diabetic patients on insulin therapy. Methods: This cross-sectional study was carried out in the Department of Endocrinology, BIRDEM General Hospital from March 2020 to August 2022. Total 384 patients with type 2 DM on insulin therapy were recruited by convenient sampling. Face to face interview was taken from the patient by following the inclusion and exclusion criteria. Patients were examined for his/her injection site, injection technique; insulin vial and syringe were also checked for any mismatch. Biochemical reports were collected from patient records. Data analysis was done by SPSS version 25 considering level of significance at 0.05. Results: The mean age of the participants was 56 ± 10, (m±SD) years. Majority (73.9%) were obese. Hypertension (70.6%) was common among the patients. Few (10.7%) patients maintained physical exercise regularly. The mean duration of DM was 12.15± 5.39 years and they were taking insulin for a mean of 4.40± 2.64 years. Most of the patients took premixed insulin (38.3%) followed by split mixed (29.7%) and basal-bolus (21.1%) regimen. Most common cause of poor glycemic control was insulin omission (46.4%). Obesity, using premixed insulin, irregular physical exercise, irregular self-monitoring of blood glucose (SMBG), not following the diet chart, no education on target glucose and insulin dose adjustment were associated with HbA1c >10%, which indicates poor glycemic control. Conclusion: Overall, lack of knowledge about glycemic control and insulin dose adjustment, insulin omission, non-adherence to the diet, irregular physical exercise act as barriers to achieve optimum glycemic control.BIRDEM Med J 2025; 15(1): 34-38